2002
DOI: 10.1097/00005373-200208000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Death among Cases Attending South Australian Major Trauma Services after Severe Trauma: The First 4 Years of Operation of a State Trauma System

Abstract: Results show a decrease in risk of death of patients attending South Australian major trauma services, from injuries of equivalent severity, during the first 4 years of operation of the State Trauma System.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 8 publications
3
33
0
Order By: Relevance
“…Our study suggests that for patients requiring emergency trauma surgery, major complica- tions and mortality are not associated with whether patients presented during the night or day, on a weekend versus a weekday, month of presentation, or year of presentation. In our analysis, sex was not a significant predictor of outcome following trauma care and this is consistent with other studies (West et al 2000, Brennan et al 2002, Croce et al 2002, Rappold et al 2002. The narrow confidence intervals surrounding many of our odds ratios provide greater confidence in these estimates of effect.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our study suggests that for patients requiring emergency trauma surgery, major complica- tions and mortality are not associated with whether patients presented during the night or day, on a weekend versus a weekday, month of presentation, or year of presentation. In our analysis, sex was not a significant predictor of outcome following trauma care and this is consistent with other studies (West et al 2000, Brennan et al 2002, Croce et al 2002, Rappold et al 2002. The narrow confidence intervals surrounding many of our odds ratios provide greater confidence in these estimates of effect.…”
Section: Discussionsupporting
confidence: 90%
“…The risk of major complications rose with procedures involving the respiratory system. As with previous analyses of trauma registries, we found that older age and higher severity of injury were predictive of increased major complications and mortality following trauma care (Brennan et al 2002). Our study suggests that for patients requiring emergency trauma surgery, major complica- tions and mortality are not associated with whether patients presented during the night or day, on a weekend versus a weekday, month of presentation, or year of presentation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A number of studies have reported the inability to collect the values necessary for the RTS in all cases with missing data ranging from 3% to 28%, [4][5][6][7][8][9][10][11] leading to a variety of mostly unvalidated methods to compensate for the loss of information, or case exclusion. These practical limitations result in a situation in which the TRISS cannot be calculated for a subset of patients (usually the most severely injured), reducing its usefulness as a standard component of trauma registries and surveillance systems.…”
Section: Components Of Trissmentioning
confidence: 99%
“…20-30 % of severe trauma cases present initially to a health care facility that is not a trauma center [10,11]. Australia has a taxpayer-funded free health care scheme (Medicare) [12].…”
Section: Current Practical Aspects In Different Trauma Systemsmentioning
confidence: 99%